Active immunization against hepatitis B virus (HBV) with low-doses of plasma-derived vaccine by intradermal route - Flair José Carrilho; Maria Lúcia Queiroz; Luiz Caetano da Silva; Luís Edmundo Pinto da Fonseca; Celso Granato; Isabel Oba; Leda Obara (Revista do Instituto de Medicina Tropical de São Paulo, 1989)
Schedule for vaccination against HBV infection has usually been based on three separate injections of 20 meg of the vaccine by intramuscular route. One of the main shortcomings to its use in large scale programs has been its high cost. Ninety out of 300 health workers were submitted to three injections of 2 meg of plasma-derived vaccine (PDV) by intradermal (ID) route on days 0, 30, and 180. Anti-HBs was detected in 74 (82.2%) after the second dose and in 80 (88.9%) after the third dose, a non-significant difference. However, levels above 10 times the cut-off were observed in 29 (32.2%) and 77 (85.5%), respectively (p < 0.001). The results showed that a low-dose schedule is effective when used in health workers and should be tried with other risk groups.